2016
DOI: 10.1007/s00438-016-1252-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of stress-associated proteins (SAPs) containing A20/AN1 zinc finger in cotton

Abstract: Stress-associated proteins (SAPs) containing the A20/AN1 zinc-finger domain play important roles in response to both biotic and abiotic stresses in plants. Nevertheless, few studies have focused on the SAP gene family in cotton. To explore the distributions and expression patterns of these genes, we performed genome-wide identification and characterization of SAPs in tetraploid Gossypium hirsutum L. TM-1 (AD1). A total of 37 genes encoding SAPs were identified, 36 of which were duplicated in the A and D sub-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 37 publications
2
39
1
2
Order By: Relevance
“…The high number of homoeologous segments present in the genome of the allotetraploid cotton results in the existence of two or more copies for most genes ( Wang et al, 2014 ; Gao et al, 2016a ). In order to obtain a functional mutant in cotton, it is imperative to edit homoeologous sequences simultaneously, and in most cases, it is possible to find highly conserved CRISPR target sequences in the homeolog genes ( Gao et al, 2016a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high number of homoeologous segments present in the genome of the allotetraploid cotton results in the existence of two or more copies for most genes ( Wang et al, 2014 ; Gao et al, 2016a ). In order to obtain a functional mutant in cotton, it is imperative to edit homoeologous sequences simultaneously, and in most cases, it is possible to find highly conserved CRISPR target sequences in the homeolog genes ( Gao et al, 2016a ).…”
Section: Resultsmentioning
confidence: 99%
“…The high number of homoeologous segments present in the genome of the allotetraploid cotton results in the existence of two or more copies for most genes ( Wang et al, 2014 ; Gao et al, 2016a ). In order to obtain a functional mutant in cotton, it is imperative to edit homoeologous sequences simultaneously, and in most cases, it is possible to find highly conserved CRISPR target sequences in the homeolog genes ( Gao et al, 2016a ). To test whether simultaneous mutation of homoeologous genes is feasible in cotton we chose Chloroplastos alterados 1 ( GhCLA1 ) which is involved in chloroplast development and have two homoeologous sequences (D10G1640 from the sub-genome D and A10G2292 from the sub-genome A, Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides Pv04, this study identified a SNP on Pv09 for quantitative resistance against race 503 in gene model Phvul.009G169600 that encodes a zinc finger protein. This gene model contains a CCCH domain and its involvement in plant disease resistance is well documented ( Deng et al, 2012 ; Gao W. et al, 2016 ; Cui et al, 2018 ). In the common bean genome only two NBS-LRR genes are located at distal end of Pv09 ( Richard et al, 2017 ) and identification of QTL against race 503 on Pv09 is interesting and warrants in silico identification of other plant disease resistance signatures such as zinc finger proteins from the common bean genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The SAP gene family members have two special ZF domains: the highly conserved A20 domain, which was first isolated in human umbilical vein endothelial cells with the characterization of a tumor necrosis factor (TNF)-α-inducible protein; and/or the AN1 domain, which is also highly conserved and first identified from Xenopus laevis animal hemisphere 1 (AN1) maternal RNA with the delineation of the ubiquitin-like protein [ 8 , 9 ]. The SAP proteins expressed in Arabidopsis thaliana (hereafter Arabidopsis ), rice ( Oryza sativa ), tomato ( Solanum lycopersicum ), and cotton ( Gossypium hirsutum ) have been classified into five groups (I through V) based on results from their phylogenetic analyses [ 10 , 11 ]. One significant feature of plant SAPs is the very frequent occurrence of intronless genes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One significant feature of plant SAPs is the very frequent occurrence of intronless genes [ 2 ]. For example, 11 rice SAP genes, 15 from desert poplar ( Populus euphratica ), and 30 from cotton lack introns and show a remarkably higher percentage of intronless genes [ 2 , 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%